Aktivitas Rutin Pasien Diabetes Mellitus Yang Berobat Ke Poliklinik Penyakit Dalam - Muriyani, Retno; Aulawi, Khudazi; Haryani, Haryani (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2007)
Please refer to the file